Health-related quality of life after segmental pedicle screw instrumentation: a matched comparison of patients with neuromuscular and adolescent idiopathic scoliosis - Soini Venla; Syvänen Johanna; Helenius Linda; Raitio Arimatias; Helenius Ilkka (United Kingdom, 2025)
Background and purpose: Progressive neuromuscular scoliosis (NMS) often requires a long instrumented spinal fusion to improve health-related quality of life (HRQoL) and sitting balance. Segmental pedicle screw instrumentation improves HRQoL in patients with adolescent idiopathic scoliosis (AIS), but data on NMS is limited. We aimed to assess the impact of spinal fusion on HRQoL in NMS patients.
Patients and methods: We conducted a retrospective case-control study with prospective data collection of NMS patients undergoing posterior spinal fusion at a tertiary level hospital in 2009-2021. 2 controls with AIS matched for sex and age were selected for each NMS patient. The Scoliosis Research Society-24 (SRS-24) questionnaire was utilized for pre- and postoperative HRQoL assessment. Follow-up time was a minimum of 2 years.
Results: 60 NMS and 120 AIS patients were included in the analysis, and the mean age (SD) at operation was 14.6 (2.7) in NMS and 15.7 (2.5) in AIS groups. Total SRS score and all domains showed a significant improvement in NMS patients (p < 0.05). Total SRS score improved more (p < 0.001), while pain score improved less (p = 0.04) in NMS (change [95% CI], 0.31 [0.05-0.58] and 0.55 [0.27-0.81]) compared with AIS (0.01 [-0.10 to 0.12] and 0.88 [0.74-1.03]). Postoperative self-image was significantly better in NMS than in AIS at 2-year follow up (p = 0.01). Pelvic instrumentation reduced improvements in the SRS domains.
Conclusion: HRQoL in NMS patients improved significantly after spinal fusion, and these benefits are comparable to those of AIS patients.